2014
DOI: 10.1161/atvbaha.114.303440
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Calcium and Phosphorus and Serum Concentration in Relation to the Risk of Coronary Artery Calcification in Asymptomatic Adults

Abstract: Objective-The current data regarding the association between calcium and phosphorus and cardiovascular disease are lacking. The aim of this study was to explore whether dietary calcium and phosphorus intake and their serum levels are associated with the prevalence of coronary artery calcification (CAC) using cardiac computed tomography in asymptomatic participants without a history of chronic kidney disease or cardiovascular disease. Approach and Results-A cross-sectional study was performed in 23 652 Korean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 41 publications
(28 reference statements)
1
68
1
1
Order By: Relevance
“…These studies demonstrate that even a serum phosphate value within the reference range (0.8-1.4mmol/l) is associated with CV calcification, as well as increased CV risk [66]. Studies of older adults and CKD patients also found a significant association between higher serum phosphate and presence and extent of calcification 18,21,22,26,28,29 , with each 0.0323mmol/l rise in serum phosphorus being associated with 6.1% higher odds of having CAC 21 . Wang et al found a gender difference; in postmenopausal women, serum phosphate was significantly higher (1.15 vs 1.17 mmol/l) in subjects with AAC, while in older men there was no association 19 .…”
Section: Calcificationmentioning
confidence: 63%
See 3 more Smart Citations
“…These studies demonstrate that even a serum phosphate value within the reference range (0.8-1.4mmol/l) is associated with CV calcification, as well as increased CV risk [66]. Studies of older adults and CKD patients also found a significant association between higher serum phosphate and presence and extent of calcification 18,21,22,26,28,29 , with each 0.0323mmol/l rise in serum phosphorus being associated with 6.1% higher odds of having CAC 21 . Wang et al found a gender difference; in postmenopausal women, serum phosphate was significantly higher (1.15 vs 1.17 mmol/l) in subjects with AAC, while in older men there was no association 19 .…”
Section: Calcificationmentioning
confidence: 63%
“…Observational studies generally show little association of calcium intake, dietary or supplemental, with coronary artery calcification (CAC) or abdominal aortic calcification (AAC) incidence or extent in older adults 4,[15][16][17][18] , although a large study showed that calcium intake was significantly higher in postmenopausal men and women without AAC at baseline and in women only after five years 19 . Koreans with the highest calcium intake (>840mg/d) also had improved serum lipid profiles 20 .…”
Section: Calcificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Diversos estudos experimentais demonstraram que uma dieta rica em fósforo promove calcificação (38,59,172,173). Já em humanos, em um estudo transversal realizado em participantes com função renal normal, não houve associação entre a ingestão de fósforo e CV (174). Contudo, nesse único estudo que avaliou a relação entre o consumo de fósforo e CV, a ingestão do mineral foi menor do que no presente projeto.…”
Section: Resultsunclassified